Keanekaragaman dan struktur komunitas semut pada perkebunan lada di Lampung - Yudiyanto, Yudiyanto; Qayim, Ibnul; Munif, Abdul; Setiadi, Dede; Rizali, Akhmad (Perhimpunan Entomologi Indonesia, 2014)
The occurrence of ants in agricultural habitat is related to the availability of food resources as well as environmental condition for its nesting site. As predator, ants play an important role on controlling pest population in agricultural habitat. The objective of this research was to study the diversity of ants in pepper plantation. The research outcome can be used as basic information for cultivation management of pepper. Ecological observation was conducted in four regencies in Lampung Province with two selected plots on each regency. On each plot, ants were sampled using pitfall traps. In total, 28 ant species were recorded from pepper field in four regencies. Two species i.e. Anoplolepis gracilipes and Solenopsis geminataare well-known as tramp and invasive species. There is significantly different of ant species composition among regencies. The occurrence of ants in pepper plantationis probably affected by habitat condition surrounding pepper plantation and precipitation.